2010
DOI: 10.1002/cncr.25027
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors involving oral chemotherapy

Abstract: BACKGROUND: Given the expanding use of oral chemotherapies, the authors set out to examine errors in the prescribing, dispensing, administration, and monitoring of these drugs. METHODS: Reports were collected of oral chemotherapy-associated medication errors from a medical literature and Internet search and review of reports to the Medication Errors Reporting Program and MEDMARX. The authors solicited incident reports from 14 comprehensive cancer centers, and also collected incident reports, pharmacy intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 24 publications
2
56
1
9
Order By: Relevance
“…This percentage was very high compared to that reported by Weingart et al in 2010, in which wrong dose involving oral chemotherapy was the most frequent type of error reported by (38.8%) 31 .…”
Section: Discussioncontrasting
confidence: 49%
“…This percentage was very high compared to that reported by Weingart et al in 2010, in which wrong dose involving oral chemotherapy was the most frequent type of error reported by (38.8%) 31 .…”
Section: Discussioncontrasting
confidence: 49%
“…Offering a streamlined way to include this information in the prescription may permit quicker prescription writing, facilitate complete prescriptions, and offer more comprehensive data capture. 3,4,6 Some free-text comments replicated information that could have been entered elsewhere, suggesting that providers were either unfamiliar with the application or simply found it to be an easier way to customize the prescription. We believe that the dosing tools that allowed weight-and BSA-based prescription improved the ease and accuracy of dose calculations, but the current data storage structure did not allow us to assess that assumption directly.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 42 US cancer centers, researchers found that most organizations lacked basic features that have long been used for infusion chemotherapy, such as required prescription elements or written informed consent. 2 In another study, investigators described oral chemotherapy errors involving each stage of the medication use process 3 and in home medication administration. 4,5 To evaluate the risks associated with oral chemotherapy, we conducted failure mode and effects analyses-a type of prospective risk assessment-for six oral chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Provide oral chemotherapy travel kits to children whose parents are separated 6-mercaptopurine oral chemotherapy incident reports. 9 Investigators at St Louis Children's Hospital (St Louis, MO) reported a reduction in the oral chemotherapy prescribing error rate from 23% to 14% concomitant with an increase in the use of standardized order forms-an intervention that resulted from an FMEA project. 10 Although the goal of our FMEA project was to identify vulnerabilities in the medication process for oral chemotherapies, this initiative also helped our organization to target improvement efforts.…”
Section: Discussionmentioning
confidence: 99%